An analog implementation of radial basis neural networks (RBNN) using BiCMOS technology - De Oliveira, J. P. [UNESP]; Oki, N. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2001)
This paper describes a analog implementation of radial basis neural networks (RBNN) in BiCMOS technology. The RBNN uses a gaussian function obtained through the characteristic of the bipolar differential pair. The gaussian parameters (gain, center and width) is changed with programmable current source. Results obtained with PSPICE software is showed.
Keywords: CMOS integrated circuits; Computer software; Electric currents; Gain measurement; Neural networks; Numerical methods; VLSI circuits; BiCMOS technology; Gaussian function; Programmable current source; Radial basis neural networks; Integrated circuit manufacture